LANGUAGE, COMMUNICATION AND MARKETING: CONTEXUALIZING THE USE OF SHENG LANGUAGE IN ADVERTISING IN KENYA. - MURIUKI, ROBERT G.M. (IJRDO - Journal of Business Management, 2015)
This paper discusses the impact of Sheng language on advertising and marketing in Kenya. Thepaper observes the evolvement of Sheng as a language in Kenya and its growing importance inadvertising and marketing. I will use secondary data to shed more light on the use of Shenglanguage in advertising in Kenya to contribute to knowledge and awareness on the issue. Whileat first Sheng was dismissed as a language of the lowly, underprivileged urban youth, it hasgrown to a language of commerce, social discourse, and politics. This has made advertisersrealize that they just have to embrace it to reach the youth who are the potential and actualconsumers of goods and services. With the population of youth estimated at 60%, it is a segmentthat advertisers cannot afford to ignore. The youth represent a significant demographic; -welleducated, high spending and care-free. Their consumption habits are exploited by advertisers andmarketers to tap them using the Sheng language with simple, catchy and memorable messages.